Building resilient urban communities - Joerin, Jonas; Shaw, Rajib; Krishnamurthy, Ramasamy R. (Emerald, 2014)
How do urban communities in Asian cities experience the impacts of urbanisation and climate change? This key issue forms the discussion point for this book. Particular reference is made to cities in India, and the capability of such urban communities of responding to climate-related disasters.
Keywords: Sustainable urban development.; Community development, Urban -- Environmental aspects.; City planning -- Environmental aspects.; Regional planning -- Environmental aspects.; elektronické knihy; electronic books